Sc2CF2/Janus MoSSe heterostructure: A potential Z-scheme photocatalyst with ultra-high solar-to-hydrogen efficiency. (18th November 2021) - Bao, Jiading; Zhu, Bao; Zhang, Fusheng; Chen, Xianping; Guo, Haojie; Qiu, Jian; Liu, Xiaodong; Yu, Jiabing
Abstract: Aroused by plant photosynthesis, Z-scheme heterostructures have been considered as a potential photocatalyst for solar-driven water splitting to solve the current energy crisis. Hence, based on first-principles calculations, we predict that Sc2 CF2 /Janus MoSSe can be used as a Z-scheme heterostructure for efficient photocatalytic water splitting. The research shows that the traditional type-II to direct Z-scheme heterostructure conversion can be realized through different stacking methods of Sc2 CF2 and Janus MoSSe. Through the built-in electric field and band bending theory, the transition path of photogenerated carriers is analyzed, which reveals the completely different photocatalytic mechanism of type-II and direct Z-scheme heterostructure. Surprisingly, the direct Z-scheme heterostructure displays a high overpotential of the hydrogen evolution reaction ( χ H 2 =1.01 eV) and the oxygen evolution reaction ( χ O 2 =1.46 eV) compared with the type II heterostructure. More importantly, the direct Z-scheme heterostructure has an ultra-high solar-to-hydrogen (STH) efficiency (36.1%), which breaks through the limitation of traditional theoretical efficiency and reveals a tremendous prospect of commercial application. Furthermore, the calculation of free energy confirms that the water splitting reaction on the direct Z-scheme heterostructure occur spontaneously under the external potential, but not for type-II heterostructure. Finally, introducing the additional electronic conductor (N-doped graphene) can accelerate the electron (hole) transfer and interlayer carrier recombination, which will further improve the photocatalytic performance of Z-scheme heterostructure. These distinctive features make Sc2 CF2 /Janus MoSSe heterostructure as promising Z-scheme photocatalyst for water splitting. Highlights: Sc2 CF2 /Janus MoSSe displays a high overpotential of the hydrogen evolution reaction and the oxygen evolution reaction. The heterostructure has an ultra-high solar-to-hydrogen efficiency. The introduction of N-doped graphene improves the photocatalytic performance of Z-scheme heterostructure.